Application of emetine in SARS-CoV-2 treatment: regulation of p38 MAPK signaling pathway for preventing emetine-induced cardiac complications. Issue 22 (17th November 2022) - Valipour, Mehdi; Irannejad, Hamid; Emami, Saeed
ABSTRACT: Emetine is one of the most highly potent anti-SARS-CoV-2 agents ever identified. In addition to having strong anti-SARS-CoV-2 activities, emetine has other valuable therapeutic effects such as strong anti-inflammatory and anti-arterial pulmonary hypertension (APH) properties, which are suitable for the treatment of COVID-19. Its proper concomitant therapeutic effect has led researchers to test this compound in clinical trials to combat COVID-19. However, due to the risks of cardiac complications, very low doses of emetine have been used in different studies, which may not have significant therapeutic effects. The p38 MAPK signaling pathway is strongly highlighted as an important operator in cardiac cellular damages such as disruption of cardiac fibroblast function and myopathy/cardiomyopathy. Inhibition of this pathway by appropriate inhibitors has also been considered by scientists as a promising strategy for the treatment of fatal host-related hyper-inflammatory immune responses following SARS-CoV-2 infection. Although remarkable stimulatory effects of emetine on activation of the p38 MAPK pathway have been reported in recent studies and strong evidence suggests that this pathway plays an effective role in the emetine's toxicities, it has not been discussed yet that emetine induced cellular cardiac complications may be due to the activation of this critical pathway. Considering these points could lead to the finding of strategies for applying the valuable potential of emetine in the treatment of COVID-19 at low risks.